The incidence of fetal malnutrition in Turkey - Özalp, İmran; Erdem, Gülşen; Ciliv, Gönenç; Köksal, Gülden; Metcoff, Jack; Costiloe, Paul; Doğramacı, İhsan (The Turkish Journal of Pediatrics, 1982)
Five-hundred twenty-five newborn babies and their mothers were studied to assess the magnitude of fetal malnutrition in Turkey by considering deviations from expected birthweight, obtained after adjusting for maternal age, height, pre-pregnancy weight, parity, gestational age and the sex of the baby. Babies whose adjusted birthweights were 1 and 2 SD below the mean of the expected birthweight were classified as moderate and severely intrauterine growth retarded, respectively. Such cases in total constitute 28.7% (151 babies) of the population studied. 60 of the cases were severely malnourished (11.4%). It was noticed that there were many babies who weighed more than 2500 gr, or above the 25th percentile by the Lubchenco criterion, yet their observed birthweights were 1 or 2 SD below their expected birthweights. It was concluded that unless the adjusting factors are taken into account, infants who are actually considerably smaller than they should be given their sex, gestational age, and characteristics of their mothers may not be recognized to be undergrown.
Keywords: fetal malnutrition; fetus; malnutrition; newborn